(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2026)
Background: Type 2 Diabetes Mellitus (T2DM) is a significant public health concern, contributing substantially to morbidity, mortality and healthcare costs. Effective management of diabetes requires a comprehensive understanding of associated comorbidities, including their type and frequency, as these conditions influence treatment outcomes and self-management practices. This study aimed to assess the pattern of comorbidities among indigenous patients with T2DM attending a secondary-level hospital in Bangladesh and to evaluate their impact on glycemic control. Materials and methods: An analytic cross-sectional study was conducted among 132 adult T2DM patients attending Rangamati General Hospital between March and August 2023. Sociodemographic and clinical data were collected using a pretested structured case record form. Comorbidities were categorized as either previously diagnosed or newly detected through routine screening during the study. Glycemic status was classified based on HbA1c levels as follows: good control (<7%), inadequate control (7–8%) and poor control (>8%). Results: Only 22 patients (16.7%) achieved good glycemic control, 33 (25%) had inadequate control and 77 (56.3%) had poor glycemic control. Comorbid conditions were identified in 88 patients (66.7%). The most prevalent comorbidity was hypertension (54.5%), followed by dyslipidemia (50.8%) ischemic heart disease (18.9%) liver disease (8.3%) stroke (7.6%) and respiratory disease (6.1%). A total of 45 patients (34.1%) had one comorbid condition, 35 (26.5%) had two and 8 (6.1%) had three or more comorbidities. Multivariatelogistic regression revealed that the likelihood of having comorbidities was significantly associated with age >60 years (OR: 3.12, 95% CI: 1.82–9.15) male gender (OR: 1.19, 95% CI: 1.03–4.25) current smoking (OR: 1.98, 95% CI: 1.01–5.25) duration of diabetes >10 years (OR: 2.11, 95% CI: 1.12–6.45) and poor glycemic control (OR: 3.01, 95% CI: 1.03–10.14). Conclusion: The study highlights a high burden of comorbidities among indigenous patients with T2DM, with a significant impact on glycemic control. These findings underscore the need for targeted intervention strategies that address both diabetes and its associated comorbidities to improve health outcomes in indigenous populations. JCMCTA 2025 ; 36 (2) : 77-84